Comparison Of Butterfly Pea Extract And Purple Sweet Potato As A Natural Indicator Of Acid-Base Solution - SITI AINUNA ROHMA; NI'MATUR ROHMA; ANGGITA SHAFIRA RIZKY; PRESTIANI PRESTIANI; DANI FIRMANSYAH; Sonny Kristianto (Journal of Natural Sciences and Learning, 2023)
Indicators are substances that can be used to show the properties of a substance through a special change in its color. The types of plants used in this study as natural indicators are found in the surrounding environment for example purple sweet potatoes (Ipomea Batatas L) and butterfly pea (Clitoria Ternatea L). This research was conducted in 5 stages: 1) cut the purple sweet potato and butterfly pea into small pieces and then mash until smooth: 2) pour 5 tablespoons of alcohol and then leave until it settles; 3) pour the extract on 3 test tubes to test acid, base, and control; 4) drip the test solution on 2 test tubes; 5) then do testing to identify discoloration in purple sweet potato extract and butterfly pea a large amount of anthocyanin content in butterfly pea (Clitoria Ternatea L) affects the results of acid and alkaline testing so that the test results on butterfly pea extract (Clitoria Ternatea L) show a clear change in color. The purpose of this study is to identify the effectiveness of purple sweet potato extract (Ipomea Batatas L) and butterfly pea (Clitoria Ternatea L) as natural indicators of acid-base so that it can be used as an alternative learning medium.